Preparation of oil palm EFB derived solid acid catalyst for esterification reaction: Effect of calcination temperature - Krishnan S.G.; Pua F.L.; Palanisamy K.; Nabihah S. (Trans Tech Publications Ltd, 2023)
Biodiesel; Calcination; Catalyst activity; Esterification; Esters; Fruits; Iron compounds; Morphology; Oleic acid; Sulfur compounds; Surface chemistry; Transition metals; Biodiesel production; Calcination temperature; Esterification of oleic acids; Esterification reactions; Oil palm empty fruit bunch; Oil palm empty fruit bunches (EFB); Solid acid catalysts; Transition metal sulfides; Palm oil